Controllable and flexible energy production in a water-based photovoltaic/thermal system - Aminou Moussavou, AA.; Raji, AK.; Adonis, M. (International Journal of Engineering and Technology, 2019)
A combined solar photovoltaic and thermal (PV/T) system is not just a product that makes our life easier, nor is it a luxury. In the future economics will make the use of the PV/T system essential. The purpose of this to improve the energy balance in a PV/T system, by control-ling the thermal energy (useful heat) production for the domestic hot water as well as the electrical production. Simulation and analysis of a simplified model of the PV/T system for cooling the PV cell and heating the working fluid inside of the absorber pipe attached at the back of the PV cell were implemented in MATLAB /Simulink software. The optimal electrical and thermal power were obtained by selecting a par-ticular value of Rse that partially converts the output of the PV cell into useful thermal energy. It was discovered that increasing the chosen value of Rse results in higher heat dissipation in the PV/T cell, an increase in thermal efficiency, and also a decrease in electrical efficiency.Â Â